Chest CT Scan for the Diagnosis of Pediatric Pulmonary TB: Radiological Findings and Its Diagnostic Significance - Buonsenso, Danilo; Pata, Davide; Visconti, Emiliano; Cirillo, Giulia; Rosella, Francesco; Pirronti, Tommaso; Valentini, Piero (Frontiers in Pediatrics, 2021)
Diagnosing active TB in children remains a clinical challenge, due to difficulties in achieving a definite microbiological confirmation, aspecific clinical manifestation, low sensitivity of chest radiography (CXR). For this reason, the use of chest computed tomography (CT) scan to evaluate suspected TB pediatric cases is increasing. We retrospectively reviewed records of patients aged <16 years diagnosed with active TB at the Pediatric Infectious Disease Unit of the Catholic University of the Sacred Heart to describe CT findings and to evaluate the need for its execution for diagnosis. In 41 cases, 7 CXR were normal (17.1%) while no CT scan was evaluated as negative. In 19 cases (46.3%), CXR was considered non-probable TB pulmonary, compared with 11 of 37 cases (29.7%) of CT. In 15 cases (36.6%) CXR was described as probable for TB pulmonary, instead 26 of the 37 cases evaluated by CT (70.3%) were classified as probable TB. We describe CT findings in patients with pediatric TB. We confirmed that CT can improve the diagnostic accuracy. In particular, the comparison between the CT and CXR ability in detecting cases of pulmonary TB in accordance with the proposed radiological probability criteria, showed a superiority of CT in detecting probable TB pictures (70.3%) compared with 36.6% of the x-Ray.